Metacognitive awareness- evaluation and implications in medical students - Panchu, Pallavi; Bahuleyan, Biju; K, Seethalakshmi; Thomas, Tom (International Journal of Research in Medical Sciences, 2017)
Background: Medical education is at cross roads today with a mismatch between students’ expectations of their performance and the reality. This led us to explore the reason for the academic decline. During our search, we found that metacognitive awareness plays a key role in moulding the learning skills of adult learners. Hence this study was conducted to evaluate the metacognitive awareness of medical students studying in the first year of MBBS. Methods: 100 first year medical students were included in the study and metacognitive awareness inventory questionnaire, a validated tool was administered to the students. This measures metacognitive knowledge and regulation. The results were obtained, tabulated and analysed. Results: Metacognitive awareness among medical students was average. Metacognitive knowledge was found to be significantly better than regulation. On comparing the genders, we note that females have better metacognitive regulation while males score higher in metacognitive knowledge which was statistically significant. Conclusions: The findings of the present study points towards the need of introduction of metacognitive strategies in the medical curriculum with more emphasis on problem based learning in order to make our learners become independent thinkers and efficient care givers.